Educated platelets promote wound healing via anti-inflammatory effect and down-regulated VEGF and MMP-9 - Yilmaz , Filiz; Ilgen , Orkun; Kurt , Sefa; Baykara , Basak; Yilmaz , Osman (Annals of Medical Research, 2022)
Aim: This study aims to investigate the effect of educated platelets histological and immunohistochemical (MMP-9 and VEGF) in wound treatment. Methods: 28 female Wistar albino 180-225 gr rats were divided into four groups randomly. The control group (C) is unburnt which blood samples are extracted or PRP with ordinary platelets. Burn group (B) is a burn group in which blood samples were extracted with the educated platelets for PRP. The Burn and uneducated platelet group (B+P) were the burn groups given PRP with uneducated platelets to their blood circulation. Burn and educated platelet group (B+EP) was the burn group given PRP with educated platelets to their blood circulation. The histological analysis was scored 14 days after injury, and MMP-9, VEGF were immunostained. Results: The results clearly showed higher reepithelialization, lower inflammation, and granulation in the B+EP group. Immunohistochemical staining for MMP-9 and VEGF in the B+EP group were statistically lower than other groups. Educated platelet treatment significantly suppressed MMP-9 and VEGF. Conclusion: Our findings suggest that educated-platelet treatment can be a promising strategy for promoting burn cutaneous wound healing. Further and more extensive clinical studies are needed to determine the effectiveness of this treatment method definitively.